Strategi Pengembangan Perluasan Akses Lembaga Keuangan: Studi Kasus di Provinsi Bali - Awirya, Agni Alam; Nugraha, Dhita Aditya; Haloho, Emy Meylita (Jurnal Ekonomi dan Pembangunan Indonesia, 2014)
Expanding financial access is one among many ways in developing financial sector. This study analyzed the connection of communities characteristics to the access of financial institution which can be used in establishing the accurate development strategy of financial inclusion. This study used three approaches: descriptive analysis, factorial analysis, and path analysis based on questionnaires distributed to 600 respondents across Province of Bali. The result of the study shows that the most important factor in developing financial access is quality, especially the speed of transaction. Moreover, individual quality improvement in either education or wealth stimulates the utilization of branchless banking services.